Modern treatment of type 2 diabetes (Conference Zone, 2022)
Modern treatment of type 2 diabetes mellitus requires a new approach to intensify therapy from the moment of diagnosis. This is supported by data showing how even a slight delay in achieving good glycemic control can contribute to an increased risk of diabetic complications.